Formulation and Evaluation of Coated Microspheres for Colon Targeting - Behin Sundara Raj, Shanthi, Rajesh Sreedharan Nair, Punitha Isaac Samraj, Vidya (Journal of Applied Pharmaceutical Science, 2013)
The purpose of this research was to formulate and evaluate coated microspheres of 5-Fluorouracil (FU) for colon targeting. Chitosan is used as polymer, which is a biodegradable polymer and undergo enzymatic degradation in the colon, so it is used as carrier to deliver the drug in the colon. Chitosan microspheres were prepared by emulsion- dehydration method using different ratios of FU and chitosan (1:2 to 1:6), stirring speed (500-2000rpm) and emulsifier concentrations (0.75% to 1.75%w/v). Eudragit S100 coating of chitosan microspheres was performed by oil-in-oil solvent evaporation method using coat: core ratio (5:1). The cumulative percentage drug release after 12 hrs was found to be in the range of 82.39 to 93.67% for F1 to F5 respectively. Among the formulations F2 was found to be the best formulation as it released 5-Fluorouracil 93.67%. The results showed that as the amount of the polymer increased the extent of drug release decreased. It was concluded from the present investigation that Eudragit coated chitosan microspheres are promising controlled release carriers for colon targeted delivery of 5-Fluorouracil.
Keywords: Eudragit,chitosan microspheres,5-Fluorouracil, colon